Transmission of Rickettsia tsutsugamushi strains among humans, wild rodents, and trombiculid mites in an area of Japan in which tsutsugamushi disease is newly endemic. - Yamashita, T (1994)
Thirty-two newly isolated strains of Rickettsia tsutsugamushi, 14 from patients with tsutsugamushi disease, 12 from wild rodents, and 6 from trombiculid mites parasitizing rodents in Gifu Prefecture, Japan, were examined for reactivities to 12 monoclonal antibodies by an indirect fluorescent-antibody test to classify their antigenicities. All of the isolates could be classified into one of six groups (KN-1, KN-2, KN-3, GJ-1, R158, and R161) according to their reactivities to the monoclonal antibodies. The KN-1 and GJ-1 strains that are prevalent among patients from Gifu Prefecture had the same reactivities as the Kawasaki and Kuroki strains, respectively, which have been isolated and are prevalent in the Miyazaki and Kagoshima prefectures in southwest Japan. The isolates from patients were different in serotype from those from rodents and mites (Leptotrombidium pallidum). The KN-2 and KN-3 strains were most prevalent among patients and among rodents and mites, respectively. No close similarity between KN-2 and other strains tested was observed. KN-3 is only a minor contributor to diseases in patients in Gifu Prefecture; however, it was proven that the same strain was prevalent in Niigata Prefecture in northern Japan. Thus, Gifu Prefecture is an area where southern, northern, and local strains are found. We hypothesize that humans are prone to infection with KN-2, GJ-1 (very similar to Kuroki), and KN-1 (very similar to Kawasaki), probably by infestation with Leptotrombidium scutellare. While both L. scutellare and L. pallidum parasitize wild rodents and may carry any rickettsial strain, the most virulent strain, KN-3, is predominant among wild rodents. Antigenic analysis using monoclonal antibodies to R. tsutsugamushi should be useful for epidemiological studies of infection with this organism.